Risk and Hazard Analysis of Riverbank Filtration Water Intakes for Water Safety Planning (Моделювання, керування та інформаційні технології, 2025)
Water Safety Plans (WSPs) are a proactive framework recommended by the World Health Organization to ensure the safety of drinking water through risk assessment and risk management along the entire supply chain – from catchment to consumer. This study presents a methodology for identifying and assessing hazards and hazardous events in riverbank filtration (RBF) water supply systems at the initial WSP development stage. A pilot investigation was conducted for a small urban settlement in the Ivano-Frankivsk region, Ukraine, where groundwater abstraction is performed from two rivers, including the Dniester. Bibliometric analysis of 3,879 publications in Scopus (as of 2025) identified key approaches and gaps in WSP-based risk assessment. Field investigations under the project Climate-Resilient Management for Safe Disinfected and Non-Disinfected Water Supply Systems - 101081980 - SafeCREW - Horizon-cl6-2022-zeropollution-01 included 2,956 measurements of physicochemical and microbiological indicators. Main hazards identified were microbial contamination during warm seasons and clogging of infiltration zones due to increased turbidity in the Dniester River. Risk assessment demonstrated medium to high levels of vulnerability associated with reservoir maintenance and seasonal water quality fluctuations. The results provide a structured basis for WSP implementation and adaptation of EN 15975-2:2022 and ISO 31000:2018 principles in small-scale water systems using riverbank filtration.